The Effect Of Mind Mapping Technique On Student’s Abiity In Comprehending Narrative Text At Eight Grade Of SMP Negeri 12 Pematang Siantar - Jeremia situmorang; Seviana Napitupuu; Asima Rohana Sinaga (CV Putra Publisher, 2024)
The aim of this research is to determine the effect of mind mapping techniques on students' abiity to understand narrative texts in class VIII of SMP Negeri 12 Pematang Siantar. It combines the quantitative research method with the qualitative design-experimental. The Quasi-experimental method is definitive because researcher treat samples differently and compare effects on those samples. By using a purposive sampling technique, the sample that wil be used in this research consists of two classes, namey VIII-3 for the Experimental class and VIII-9 for the control class at SMP Negeri 12 Pematang Siantar. This data was obtained from the resuts of students' research before and after the research. Researcher found that the use of Mind Mapping Techniquu had a major impact on students' abiity to use the teephone. In particuar, they found the general structure of stories reated to class VIII at SMP Negeri 12 Pematang Siantar. Mind Mapping technology also heps students understand the material, makes students more active in class, and creates an inteligent learning atmosphere for students. With a significance leve of 5%, the T-calcuated value is greater than the T-table (2.41 higher than 1.672), and the post-research average score for the experimental class is 78.16 and the post-research average score for the control class is 64.66. The standard error of mean difference is 5.32. It also shows that (Ho) is rejected and (Ha) is accepted.